(untitled) (Al-Qamar, 2022)
The Topic of Hermaphrodite is one of the real issues in society, and the jurists have been exposed to it in many of their books and to clarify the important issues in it. That is because it contains problems that lead to error and confusion between the permissible and the forbidden. And I ask God Almighty that this research be based on these problems and clarify the ruling concerning them. For this reason, the research was divided into three topics. In the first topic, I talked about the definitions of the hermaphrodite, and after fully examining the opinions of the jurists in defining the concept of the hermaphrodite, I showed the collector and the determinant of the meaning of the hermaphrodite for the meaning to be an introduction to the subject we are dealing with. As for the second topic, it includes the distribution of the hermaphrodite, its division of the hermaphrodite and the hermaphrodite not forming, and an explanation of what is known to be male or female. As for the third topic, it is the provisions specific to the hermaphrodite, and it includes the important issues in its subject, which are the provisions related to prayer, his marriage, his inheritance, his circumcision, his wearing of gold and silk, his washing, shrouding and burial.